Land-use changes in Coastal Alentejo. Methodological approach to understand the interactions Nature/Society in coastal areas - Lourenço, Nelson (2012)
Being land use and land use changes one of the main issues integrating the large debate on sustainable development, its analysis demand clearly an integration of spatial / landscape data with the socio-economic data type which has been recently widely recognised. The question is how this integration is possible, and how can it best be achieved. Moreover, the land use changes studies must be a contextualised analysis centred in the individual inside the context where he acts. This departing point assumes that the individual induces the land use changes but he also reflects the changes made by other agents that intervene, directly or indirectly, in the land use. This paper deals with the identification of the required conditions for a real integration of disciplines, without which an integrated analysis may not be possible. To do so we are searching the information that is necessary to fulfil the objective of an integrated methodology.